A new fermented beverage from sugarcane (Saccharum officinarum L.) molasses: Analysis of physicochemical properties and antioxidant capacity, and comparison with other industrial alcohol products. (June 2020) - Samaniego-Sánchez, C.; Marín-García, G.; Quesada-Granados, J.J.
Abstract: A new alcoholic beverage made from sugarcane ( Saccharum officinarum L.) molasses was studied and compared with analogous products. Three honey meads and two beverages obtained from sugarcane molasses were analysed to determine physicochemical characteristics, the Folin-Ciocalteu index, tannins, flavonoids and antioxidant capacity. The results obtained show that sugarcane molasses share some physicochemical characteristics with beer and red wine (%V/V ≈ 8.9 with red wine; acidity (g tartaric acid/L) ≈ 2.7 with beer; pH ≈ 4.0 with beer and honey mead; reducing sugars (g/L) ≈ 3.0 with red wine). The remaining parameters, however, differ statistically from those of beer, red wine and honey mead. Multivariate analysis confirmed the differences found between these industrial alcoholic products and sugarcane molasses mead. We conclude that the sugarcane molasses product is a valid alternative for the consumer of fermented alcoholic beverages and an interesting use of a by-product of the sugar cane industry. Highlights: A new sugarcane molasses beverage was studied/compared with analogous products. Sugarcane molasses meads had a higher antioxidant capacity than the honey ones. The values of phenols are higher in the sugarcane meads than in the honey ones. Sugarcane mead is statistically different from similar alcoholic beverages. Sugarcane mead is a new alternative to wine, beer or honey mead.